Empirical model for evaluating situational efficiency in top level handball - Foreti, N.; Rogulj, N.; Papi, V. (International Journal of Performance Analysis in Sport, 2013)
The main research goal of the study was to determine the quantitative contribution of situational activities of playing positions and game phases depending on the match result in top level handball. The model for evaluating situational efficiency is defined and software application is constructed based on the notational parameters and subjective assessments of experts. For this purpose, 101 matches, played at the World Championships held in Croatia in 2009, were analyzed and 19 experts were interviewed. Events notation was done by using Match Analysis System software. Set of prediction variables represents 48 variables, 9 out of which are in relation to position defence, 11 to the goalkeeper position, 16 to the position offence, 5 to the transition defence and 7 to the transition offence. Calculated coefficients for individual playing positions were the basis for setting the evaluation model of situational efficiency. According to this model, the overall efficiency of players is expressed as the relative value of the sum of defence and offence scores of players weighed with the coefficient of importance of each phase of the game. Applicability of the study was confirmed by evaluating the models that have shown a high correlation with ratings of an independent handball expert (r=0,79).